Effect of Intravenous Lidocaine on Postoperative Recovery of Patients Undergoing Mastectomy: A Double-Blind, Placebo-Controlled Randomized Trial. Issue 6 (1st November 2014) - Terkawi, Abdullah S.; Durieux, Marcel E.; Gottschalk, Antje; Brenin, David; Tiouririne, Mohamed
Abstract : Background: One of the modalities of treatment for breast cancer surgery pain is opioids, and opioids are associated with adverse effects such as itching and postoperative nausea and vomiting (PONV). Intravenous (IV) lidocaine has been shown to reduce opioid consumption and to improve overall postoperative outcomes in abdominal surgery. In this study, we tested the effect of intraoperative IV lidocaine infusion on the quality of postoperative recovery after breast cancer surgery. Methods: Seventy-one patients undergoing breast cancer surgery were randomly assigned to receive either placebo (group P; n = 34) or IV lidocaine (group L; n = 37, bolus 1.5 mg/kg at induction, then infusion at 2 mg/kg/h, stopped 2 hours after the end of surgery) in a prospective double-blind design. Intraoperative and postoperative morphine consumption was calculated. Postoperative pain scores, PONV, and fatigue were assessed at 2, 24, and 48 hours after surgery. Duration of postoperative hospital stay was recorded. Results: Demographics were the same between the groups. There was no statistically significant difference in intraoperative or postoperative morphine consumption ( P = 0.188 and P = 0.758) between groups. Overall pain scores either at rest or activity ( P = 0.348 and P = 0.810, respectively), PONV ( P = 0.350), fatigue ( P = 0.758), or duration of postoperative hospital stay ( P = 0.218) were not statistically different. Conclusions: Our findings did not show a significant effect of IV lidocaine during breast cancer surgery on opioid consumption, pain score, PONV, or fatigue, indicating that the benefit of this approach does not generalize across all types of surgery.